Bright‐band detection from radar vertical reflectivity profiles - Ian Cluckie (International Journal of Remote Sensing, 2007)
The use of quantitative scanning weather radar for precipitation measurements is a vital element of modern hydrology and limits the development of all distributed models of catchment behaviour. The presence of the so‐called bright band (or melting layer) contaminates the quantitative precipitation estimates and has delayed the widespread take‐up of radar‐based precipitation estimates in operational models. The study of the Vertical Reflectivity Profile (VRP) of precipitation is important in order to develop algorithms to correct scanning weather radar measurements for the variation of the VRP at long ranges. Therefore, this paper presents an algorithm to detect the extent of the bright band using high‐resolution VRP's. The boundaries of the bright band are identified by a new algorithm which utilizes a rotational coordinate system for identifying the upper and lower parts of the bright band. This overcomes some of the difficulties experienced when using the gradient of the reflectivity in conventional bright‐band detection algorithms. The reflectivities above, within, and below the bright band are then used to construct idealized VRP's to correct scanning weather radar measurements.